Sharing Power dalam Kepemimpinan Kristen: Kajian Teologis Dari Filipi 2:3-4 - Afaradi, Asep (Integritas: Jurnal Teologi, 2024)
The crisis in the context of Christian leadership today involves issues such as emphasis on authoritarian leadership, maintenance of the status quo, lack of leadership capacity, and ambition for domination. Therefore, the focus of this research is to propose a new paradigm related to the development of leadership principles based on sharing power within the church environment. The research method used is a qualitative approach. The research findings indicate that Christian leadership based on the principle of shared power reflects the love of Christ who serves with humility, prioritizes the interests of others over personal interests, and is willing to share power with the congregation. By applying these principles, a strong relationship is formed between leaders and the congregation, thereby strengthening spiritual growth and unity within the church community.